The Problem of Foreign Influences On Early Islamic Law - Akh. Minhaji (Al-Jami'ah Research Centre, 1992)
The Origin of Islamic doctrine is the subject of one of the most serious debates among Islamic scholars. Wellhausen, Andrae, and Ahrens were of the opinion that Christianity “played the Decisive role in the birth of Islam. Richard Bell went even further by saying that popular influence, theology, and the transmission of Greek Philosophy were the important areas in which Christianity affected the development of Islamic teaching. Torry, on the other hand, contends that the doctrine that the basis of Islam was mainly Christianity is completely refuted by the evidence which the Qur’an furnishes and by the materials gathered from pre-Mohammedan Arabia. Moreover, according to him, “…in the Koran itself there is no clear evidence that Mohammed had ever received instruction from a Christian teacher…”. Islamic law, as the central core of Islamic doctrine, is also affected by such controversy. During the last few years there has been a serious discussion among Islamic scholar on the origin and the early development of Islamic law. In 1950, at the third International Congress of Comparative Law, Joseph Schacht addressed the problem in this paper entitled “foreign Elements in Ancient Islamic Law, which investigated the influence of Roma law on Islamic law. Shortly afterwards, S. Vesey Fitzgerald published an article entitled “The Alleged debt of Islamic to Roma Law.” Contrary to Schacht, Fitzgerald contended that Islamic law was not influenced by Roma law. The present essay Corroborates Schacht’s conclusion, and I shall argue that the influence on Islamic law came not only from Roma law but also from other source such as pre-Islamic Arab tradition and Judaic law.